2021
DOI: 10.1101/2021.07.21.453218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary conservation of centriole rotational asymmetry in the human centrosome

Abstract: Centrioles are formed by microtubule triplets in a nine-fold symmetric arrangement. In flagellated protists and in multiciliated cells, accessory structures tethered to specific triplets render the centrioles rotationally asymmetric, a property that is key to cytoskeletal and cellular organization in these contexts. In contrast, centrioles within the centrosome of animal cells display no conspicuous rotational asymmetry. Here, we uncover rotationally asymmetric molecular features in human centrioles. Using ult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Such a radial structure has never been observed in the centriole, but it is likely that another type of assembly exists there. Indeed a recent study has shown that C2CD3 and LRRCC1 also localize at the lumenal distal end of the human centriole (Gaudin et al , 2022), similarly to SFI1 and Centrin, and delineate a structure reminiscent of the acorn, a filamentous density observed by electron microscopy in pro and mature Chlamydomonas basal bodies (Geimer, 2004; Gaudin et al , 2022). In addition, the acorn is accompanied by a V‐shaped filament system that has been proposed to be composed of Centrin (Geimer & Melkonian, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Such a radial structure has never been observed in the centriole, but it is likely that another type of assembly exists there. Indeed a recent study has shown that C2CD3 and LRRCC1 also localize at the lumenal distal end of the human centriole (Gaudin et al , 2022), similarly to SFI1 and Centrin, and delineate a structure reminiscent of the acorn, a filamentous density observed by electron microscopy in pro and mature Chlamydomonas basal bodies (Geimer, 2004; Gaudin et al , 2022). In addition, the acorn is accompanied by a V‐shaped filament system that has been proposed to be composed of Centrin (Geimer & Melkonian, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Such a radial structure has never been observed in the centriole, but it is likely that another type of assembly exists there. Indeed a recent study has shown that C2CD3 and LRRCC1 also localize at the luminal distal end of the human centriole (Gaudin et al, 2021), similarly to SFI1 and centrin, and delineate a structure reminiscent of the acorn, a filamentous density observed by electron microscopy in pro-and mature Chlamydomonas basal bodies (Gaudin et al, 2021;Geimer, 2004). In addition, the acorn is accompanied by a V-shaped filament system that has been proposed to be composed of centrin (Geimer and Melkonian, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, LRRCC1 has recently been shown to localise asymmetrically within the lumen of human centrioles with the position of procentriole assembly being nonrandom with respect to this asymmetric mark (Gaudin et al, 2021). Thus, although the molecular nature may vary, it's possible that a non-random positional preference in daughter centriole assembly is an important conserved feature of centriole duplication.…”
Section: Discussionmentioning
confidence: 99%